Analysis of black soil compaction with driver-agricultural machinery-soil system under corn sowing with high-power tractor in Northeast China - Yang, Xiao; Zhai, Zhiqiang; Guo, Weijie; Li, Wenjie; Yang, Minli; Song, Zhenghe (International Journal of Agricultural and Biological Engineering, 2023)
Soil compaction leads to crop yield reduction in Northeast of China. The interaction mechanism of driver-agricultural machinery-black soil is not clear. A comprehensive field experiment of 4 hm2 of maize seeding was carried out in Baiquan County Cooperative. The results showed that the average increase rates of soil compaction before and after sowing were 118.82% and 71.02%. The SEM showed that waist fatigue had the greatest impact on soil compaction, and the unit fatigue of waist caused 1.51 and 1.27 unit compactions to the soil at the depths of 10 cm and 20 cm. The neck, waist, arm and leg fatigue of drivers increased the surface soil compaction by 1.83, 1.76, 1.78 and 1.55 units, and the deep soil compaction by 1.65, 1.58, 1.60 and 1.40 units. The results can provide a reference for the integration of human factor efficiency and conservation tillage.Keywords: agriculture ergonomics, structural equation model, black soil compaction, sowing, high-power tractorDOI: 10.25165/j.ijabe.20231604.7284Citation: Yang X, Zhai Z Q, Guo W J, Li W J, Yang M L, Song Z H. Analysis of black soil compaction with driver-agricultural machinery-soil system under corn sowing with high-power tractor in Northeast China. Int J Agric & Bio Eng, 2023; 16(4): 168-173